2003
DOI: 10.1124/jpet.102.045716
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlocomotive and Discriminative Stimulus Effects of Cocaine Are Under the Control of Serotonin2C(5-HT2C) Receptors in Rat Prefrontal Cortex

Abstract: The serotonin 2C (5-hydroxytryptamine 2C ; 5-HT 2C ) receptor (5-HT 2C R) is found in abundance in dopamine (DA) mesocorticolimbic pathways and is one of the important target proteins that modulates the behavioral effects of cocaine. In the present study, the hypothesis was tested that the 5-HT 2C R in the prefrontal cortex (PFC) may control either spontaneous or cocaineevoked locomotor activity as well as the discriminative stimulus properties of cocaine. In male Sprague-Dawley rats implanted with bilateral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
79
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 58 publications
11
79
0
Order By: Relevance
“…Further studies suggest that these effects are mediated, at least in part, by 5-HT2C receptors in the VTA (Fletcher et al, 2004). Additionally, there is evidence that constitutive or agonist-induced activity at 5-HT2C receptors in the PFC is capable of attenuating the hyperlocomotive and discriminative stimulus effects of cocaine (Filip and Cunningham, 2003). Taken together, these data suggest a role for the 5-HT2C receptor in the treatment of psychostimulant drug abuse/addiction.…”
Section: Mesocortical Systemmentioning
confidence: 85%
See 1 more Smart Citation
“…Further studies suggest that these effects are mediated, at least in part, by 5-HT2C receptors in the VTA (Fletcher et al, 2004). Additionally, there is evidence that constitutive or agonist-induced activity at 5-HT2C receptors in the PFC is capable of attenuating the hyperlocomotive and discriminative stimulus effects of cocaine (Filip and Cunningham, 2003). Taken together, these data suggest a role for the 5-HT2C receptor in the treatment of psychostimulant drug abuse/addiction.…”
Section: Mesocortical Systemmentioning
confidence: 85%
“…We have recently shown that infusions of SB 206553 directly into the PFC did not alter basal, K + -stimulated, or stress-induced cortical DA release (Alex et al, 2005;Pehek et al, 2006). Cortical 5-HT2C receptors do modulate DAmediated behaviors for intracortical infusions of a 5-HT2C antagonist potentiated the hyperlocomotion induced by a systemic injection of cocaine (Filip and Cunningham, 2003). However, current evidence suggests that this effect is not mediated by alterations in extracellular DA in the PFC (Alex et al, 2005).…”
Section: Mesocortical Systemmentioning
confidence: 92%
“…Other sites, such as the PFC, may be involved as well. Inactivation of this area attenuates reinstatement induced by contextual cues (Fuchs et al, 2005), and the locomotor stimulant, and discriminative stimulus properties of cocaine are reduced by activation of 5-HT 2C receptors in the PFC (Filip and Cunningham, 2003), suggesting a functional role for these cortical receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the behavioral effects of psychomotor stimulants such as cocaine involve increased activity of mesolimbic dopamine function (eg, Callahan et al, 1991;Kelly and Iversen, 1976;Pettit et al, 1984). A number of studies have now shown that 5-HT 2C receptor agonists attenuate cocainestimulated locomotor activity (Filip et al, 2004;Filip and Cunningham, 2003;Fletcher et al, 2004;Grottick et al, 2000). Ro60-0175 also reduced responding for intravenous infusions of cocaine under both fixed ratio (FR) and progressive ratio schedules of reinforcement (Grottick et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Within the substantia nigra/ventral tegmentum, 5-HT 2C receptors are expressed on inhibitory GABA-ergic interneurons (Eberle-Wang et al, 1997). 5-HT 2C receptor stimulation inhibits reward system-related behaviors including cocaine-induced hyperlocomotion (Filip and Cunningham, 2003;Grottick et al, 2000). 5-HT 2C receptor blockade increases both dopaminergic cell firing and DA release in nucleus accumbens and frontal cortex (Alex et al, 2005;Millan et al, 1998).…”
Section: Typical Antipsychotic Medicationsmentioning
confidence: 99%